The Relationship between Epistemological Beliefs and Assessment Conceptions among Pre-Service Teachers - Tessema Girma; Michael Kassa; Areaya Solomon (Open Education Studies)
This study examined the relationship between pre-service teachers’ epistemological views and their assessment conceptions, as well as how epistemological beliefs and their components contribute to the variation in their assessment conceptions. Utilizing a quantitative descriptive correlational research design, data were collected from 197 pre-service teachers at Fitche College of Teacher Education in Ethiopia through the Epistemological Belief Questionnaire and Assessment Conception Questionnaire. The analysis involved correlation and multiple regression techniques. The findings revealed a significant association between epistemological beliefs and assessment conceptions with a strong correlation in the ‘omniscient authority’ and ‘simple knowledge’ sub-dimensions. However, the ‘quick learning’ sub-dimension exhibited a weaker relationship. Furthermore, pre-service teachers showed a high level of agreement with the concepts of improvement and school accountability, whereas agreement with the irrelevance of assessment was moderate, yet students’ accountability was not significantly related to their epistemological beliefs. Generally, the findings of the study uncovered a meaningful correlation between pre-service teachers’ epistemological beliefs and their conceptions of assessment. This study’s findings could highlight the need to incorporate progressive assessment concepts and advanced epistemological beliefs into educational programs such as teacher education to improve pre-service teachers’ professional beliefs and competencies that would have cascaded effects on the school teaching-learning.